Drying and wetting soil-water characteristic curves of sandy soils - Jasmine Sadimin (2018)
In unsaturated soil mechanics, the mechanical behaviour of the soil is governed by the net normal stress and matric suction. Matric suction is the difference between pore air and pore-water pressure. This value often changes due to change in the moisture content within the unsaturated soil caused by climatic changes. The relationship between the moisture content and matric suction is represented by the soil-water characteristic curve (SWCC). In reality, the drying and wetting processes will produce two distinct SWCC and the difference between these two curves is known as the hysteresis. This research aims to further study the soil-water characteristic in the negative matric suction region. Particularly the effect of density and sand gradation on the SWCC. Two sands of different gradation was exposed to different matric suction using the flexible wall SWCC set-up and the Tempe cell was used to investigate the drying SWCC at zero net confining pressure. Findings from this experiment show that at high matric suction values, the grain size and density of the sand do not affect the wetting SWCC. However at matric suction lower than 0.5 kPa , there is a greater water retaining ability observed within finer grain sized sand particles. The rate of change in the cumulative mass of water retained is said to be related to the grain size at low matric suction. Finer grained sand can hold more water faster. The air entry value (AEV) of sand was found to be relatively low at approximately 0.5 to 1 kPa matric suction.